2019
DOI: 10.1007/s10068-019-00713-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial transglutaminase and alginate on the water-binding, textural and oil absorption properties of soy patties

Abstract: This study investigated the effects of microbial transglutaminase (TG) and sodium alginate (AL) on the water-binding, textural and oil absorption properties of soy patties as a representative meat analog. The addition of TG increased all textural parameters and decreased the expressible moisture of the product. Alternately, AL showed the high water-binding properties of soy patties but caused a decrease in the textural parameters of the product. Both TG and AL were effective in reducing oil absorption during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…Furthermore, variations in chemical composition, including moisture, fat, and fiber content in different formulations, could be the basis for the vast differences in physicochemical characteristics that might occur due to the substitution of beef with TVP [11]. Inconsistent with the current study, it has been confirmed that lower moisture content in soy-based patties caused an increase in protein and lipid indices [24]. Moreover, Lin and Mei [25] and Danowska [26] reported similar findings in low-fat meat batters and pork patties with low-fat soy protein added, respectively.…”
Section: Proximate Analysissupporting
confidence: 69%
“…Furthermore, variations in chemical composition, including moisture, fat, and fiber content in different formulations, could be the basis for the vast differences in physicochemical characteristics that might occur due to the substitution of beef with TVP [11]. Inconsistent with the current study, it has been confirmed that lower moisture content in soy-based patties caused an increase in protein and lipid indices [24]. Moreover, Lin and Mei [25] and Danowska [26] reported similar findings in low-fat meat batters and pork patties with low-fat soy protein added, respectively.…”
Section: Proximate Analysissupporting
confidence: 69%
“…Usually, these types of meat-analog products are made from texturized vegetable protein (usually soy) obtained through low-moisture extrusion using a combination of hydrocolloids, such as carrageenan and methylcellulose [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that using MTG and phosphates increased textural parameters (Carballo et al., 2006; Tseng et al., 2000). In studies, MTG used in soy meatballs, sausages, chicken burgers, and minced fish has similarly improved textural properties of those meat products (Gultekin et al., 2012; Lee & Hong, 2020; Moreno et al., 2010; Uran & Yilmaz, 2018). It has been reported that MTG increases the gel‐forming ability of meat proteins in products such as sausages, ham and burgers (Mostafa, 2020).…”
Section: Resultsmentioning
confidence: 99%